Mechanical Properties of Giomer After Immersion in Carbonated Drinks - Kovianti, Cindy; Tjandrawinata, Rosalina; Eddy, Eddy (Indonesian Dental Association, 2022)
Introduction: Giomer is a resin-based restorative material consisting of prereacted glass ionomer (PRG) filler which can release fluoride. Carbonated beverages, popular beverages which contain acids that rich in H+ ions, can diffuse into the resin-based restoration and cause high solubility. Objective: To analyze the effect of immersion in carbonated drinks on water absorption and diametral tensile strength of giomer. Methods: Giomer was packed into a stainless-steel mold to obtain sample with diameter of 6.0±0.03mm and height of 3.0±0.09mm. The samples were divided into 2 groups for water absorption test and 3 groups for diametrical tensile strength test. Ten samples of giomer were soaked in artificial saliva for 4 days as a control group, 10 giomer samples were immersed in carbonated drinks for 6 hours, then replaced with artificial saliva for 18 hours and repeated for 4 days as a treatment group, and 10 samples of giomer were used as immediate group for direct diametral tensile strength test. Samples were incubated at 37°C. Results: Mann-Whitney test showed no significant difference (p>0.05) in giomer absorption between the control group (0.99±0.54%) and the treatment group (2.37±2.62%). One Way ANOVA test showed significant difference (p<0.05) in giomer diametral tensile strength among the immediate group (29.6±3.7MPa), the control group (51.1±3.9MPa) and the treatment group (44.8±5.3MPa). Conclusion: Immersion in carbonated beverages did not show significant difference with artificial saliva for the water absorption ability of giomer. However, the diametral tensile strength of giomer decreased after immersion in carbonated beverages for 24 hours.